THE EFFECT OF INQUIRY BASED LEARNING ON THE REASONING ABILITY OF GRADE VII STUDENTS ABOUT HEAT CONCEPT - Damawati, N. A. C.; Juanda, E. A. (Jurnal Pendidikan Fisika Indonesia, 2016)
This study aimed to analyze the effect of Inquiry Based Learningon the reasoning ability of grade 7 students about heat concept. This study is a quasi-experimental research design with non-equivalent post-test only controls group design. Two groups of seventh grade students were included as samples, which receive the experimental class of Inquiry Based Learning treatment while the other group acted as a control group who received the learning process in accordance with the applicable provisions of the curriculum. The data collected in this study is the students reasoning ability which obtained from the test of reasoning ability. Data were analyzed using descriptive statistics and statistical parametric t-test. Results of independet research shows that there are significant differences in reasoning abilities between the experimental class and control class. In this research, the experiment class perform more better reasoning skills than the control class.Penelitian ini bertujuan untuk menganalisis pengaruh Inquiry Based Learning terhadap kemampuan penalaran siswa kelas VII pada materi Kalor. Penelitian ini merupakan penelitian eksperimen semu dengan rancangan non-equivalent post-test only control group design.Â  Dua kelompok siswa kelas VIIÂ  dilibatkan sebagai sampel penelitian, dimana kelas eksperimen menerima perlakuan Inquiry Based Learning sementara kelompok lainnya bertindak sebagai kelas kontrol yang menerima proses pembelajaran sesuai dengan ketentuan kurikulum yang berlaku di sekolah tempat penelitian dilaksanakan. Data yang dikumpulkan dalam penelitian ini adalah kemampuan penalaran siswa yang diperoleh dari hasil tes kemampuan penalaran. Data dianalisis dengan menggunakan statistik deskriptif dan statistik parametrik Independent t-test. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan penalaran yang signifikan antara kelas eksperimen dan kelas kontrol Kelas eksperimen menunjukkan kemampuan penalaran yang lebih baik dibandingkan dengan kelas kontrol.